Combinational treatment of all‐trans retinoic acid (ATRA) and bisdemethoxycurcumin (BDMC)‐induced apoptosis in liver cancer Hep3B cells - Huang, Ting‐Yi; Peng, Shu‐Fen; Huang, Yi‐Ping; Tsai, Chang‐Hai; Tsai, Fuu‐Jen; Huang, Chih‐Yang; Tang, Chih‐Hsin; Yang, Jai‐Sing; Hsu, Yuan‐Man; Yin, Mei‐Chin; Huang, Wen‐Wen; Chung, Jing‐Gung (Journal of food biochemistry, 2020)
The effects of two‐drug combination, all‐trans retinoic acid (ATRA) and bisdemethoxycurcumin (BDMC), on apoptosis induction of liver cancer cells were investigated in human liver Hep 3B cells. Two‐drug combination caused a more effective decrease in cell viability and in induction of S phase arrest, DNA damage, and cell apoptosis than that of ATRA or BDMC only. Also, the two‐drug combination caused more cells to undergo significantly increased ROS productions when compared to that of ATRA or BDMC only. Results of Western blotting demonstrated that two‐drug combination increased expressions of Fas, pro‐apoptotic proteins, and active form of caspase‐3 and ‐9, but decreased that of anti‐apoptotic proteins and XIAP than that of ATRA or BDMC only in Hep 3B cells. In conclusion, ATRA combined with BDMC enhance cell apoptosis and associated protein expression in Hep 3B cells. Practical applications Bisdemethoxycurcumin (BDMC) derived from natural plants, turmeric (Curcuma longa), which had been used for Asia food for thousands of years. All‐trans retinoid acid (ATRA) is currently used as a primary treatment for patients with acute promyelocytic leukemia. In previous study, ATRA and BDMC were reported to have anti‐inflammatory and anticancer effects. Our results showed that treatment of ATRA combined with BDMC showed more effectively apoptosis than that of ATRA or BDMC only in Hep 3B cells. The findings also provided possible pathways concerning the induction of liver cancer cell apoptosis. We conclude that ATRA combined with BDMC may be potent anticancer agents or adjuvants for liver cancer therapy in the future.